Fatal neonatal nephrocutaneous syndrome in 18 Roma children with EGFR deficiency. Issue 6 (6th April 2020) - Mazurova, Stella; Tesarova, Marketa; Zeman, Jiri; Stranecky, Viktor; Hansikova, Hana; Baxova, Alica; Giertlova, Maria; Lastuvkova, Jana; Chovanova, Vanda; Rusnakova, Simona; Knapkova, Maria; Minarik, Gabriel; et al.
Abstract: Epidermal growth factor receptor (EGFR) is a transmembrane glycoprotein with tyrosine‐kinase signaling activity, involved in many cellular functions including cell growth and differentiation. Germ line loss‐of‐function mutations in EGFR lead to a severe neonatal skin disorder (Online Mendelian Inheritance in Man #131550). We report 18 premature Roma children from 16 families with birthweights ranging 440–1470 g and multisystem diseases due to the homozygous mutation c.1283G˃A (p.Gly428Asp) in EGFR. They presented with thin, translucent, fragile skin (14/15), skin desquamation (10/17), ichthyosis (9/17), recurrent skin infections and sepsis (9/12), nephromegaly (10/16) and congenital heart defects (7/17). Their prognosis was poor, and all died before the age of 6 months except one 13‐year‐old boy with a severe skin disorder, dentinogenesis imperfecta, Fanconi‐like syndrome and secondary hyperaldosteronism. Management of ion and water imbalances and extremely demanding skin care may improve the unfavorable outcome of such patients.